Anabolic steroid use among gay and bisexual men living in Australia and New Zealand: Associations with demographics, body dissatisfaction, eating disorder psychopathology, and quality of life. (1st December 2017) - Griffiths, Scott; Murray, Stuart B.; Dunn, Matthew; Blashill, Aaron J.
Highlights: The prevalence of anabolic androgenic steroid (AAS) use was 5.2%. The prevalence of thinking about using AAS was 25.4%. Non-Australian/New Zealander men were more likely to use AAS (7.0% vs. 4.2%). Eating disorder psychopathology was associated with AAS use. Body image and eating disorder psychopathology were associated with AAS thoughts. Abstract: Background and aims: Gay and bisexual men may be at heightened risk for using anabolic androgenic steroids (AAS). Few studies, however, have examined AAS use among gay and bisexual men living in countries outside the United States. In addition, few studies have explored the potential associations of AAS use with body image concerns beyond muscularity, including height and genitals, or with eating disorder symptoms and quality of life. Thus, we examined the associations of AAS use, and of thoughts about using AAS, with body image, eating disorder symptoms, and quality of life among gay and bisexual men living in Australia and New Zealand. Methods: A sample of 2733 gay and bisexual men completed an online survey promoted by paid nationwide advertisements to users of geosocial-networking smartphone applications. Results: The prevalence of AAS use, and of thoughts about using AAS, were 5.2% (95% confidence interval [CI]: 4.4%, 6.1%) and 25.4% (95% CI: 23.8%, 27.1%), respectively. Multivariate analyses revealed that more frequent thoughts about using AAS were associated with being older, taller, and experiencing greater dissatisfaction with muscularity and height, less dissatisfaction with body fat, greater eating disorder symptoms, and lower subjective quality of life. Actual AAS users were more likely to be older, from a non-Australian/New Zealander cultural background, experiencing less dissatisfaction with body fat, and experiencing greater eating disorder symptoms. Conclusions: Psychopathology related to body image and eating disorders are associated with AAS use among gay and bisexual men living in Australia and New Zealand.